3D study of the vibrational behaviour of lithic flint blades - Rostand B. Tayong; Tatsuki Fushimi; Ole Grøn; Lars O. Boldreel (Results in Engineering, 2023)
Stone Age sites are well known to often contain many lithic flint blades and flakes, which may provide important information about early European Stone Age cultures and their environment. Understanding the mechanical behaviour of lithic flint blades represents an important problem for scientists in general and archaeologists in particular. In this study, the structural behaviour of lithic flint blades is studied. Ten specimens with different geometric shapes (tilted, curved, with bumping surfaces) were studied and tested. Their natural frequencies, damping ratios, and mode shapes (that is how the specimen deforms under any external excitation) are estimated using two models: an analytical model that accounts for the specimen's curvature and a 3D Finite Element (FE) method. Advanced experimental methods, including ultrasound techniques, were used to measure the mechanical properties of the specimens. The experimental set-up was built around a laser vibrometer that measured the specimen's displacement. The model predictions were compared with the experimental data to validate their effectiveness. A good agreement is observed between the models and the real data. It is particularly observed that despite their complicated geometries, the specimens still follow a structured pattern in their dynamic response. The presented study supports the use of acoustic methods as an effective tool to characterize and detect submerged prehistoric materials. This work contributes to the dynamic characterization of submerged Stone Age materials.